Effect of Essential Oils on the Release of TNF-α and CCL2 by LPS-Stimulated THP‑1 Cells - Maria Graça Miguel; Carina Isabel da Silva; Luana Farah; Fernão Castro Braga; Ana Cristina Figueiredo (Plants, 2020)
Plants and their constituents have been used to treat diverse ailments since time immemorial. Many plants are used in diverse external and internal formulations (infusions, alcoholic extracts, essential oils (EOs), etc.) in the treatment of inflammation-associated diseases, such as those affecting the respiratory tract or causing gastrointestinal or joint problems, among others. To support the traditional uses of plant extracts, EOs have been assessed for their alleged anti-inflammatory properties. However, the effect of EOs on the release of cytokines and chemokines has been much less reported. Considering their traditional use and commercial relevance in Portugal and Angola, this study evaluated the effect of EOs on the in vitro inhibition of the cytokine tumor necrosis factor-α (TNF-α) and the chemokine (C-C motif) ligand 2 (CCL2) by lipopolysaccharide (LPS)-stimulated human acute monocytic leukemia cells (THP-1 cells). Twenty EOs extracted from eighteen species from seven families, namely from Amaranthaceae (Dysphania ambrosioides), Apiaceae (Foeniculum vulgare), Asteraceae (Brachylaena huillensis, Solidago virgaurea), Euphorbiaceae (Spirostachys africana), Lamiaceae (Lavandula luisieri, Mentha cervina, Origanum majorana, Satureja montana, Thymbra capitata, Thymus mastichina, Thymus vulgaris, Thymus zygis subsp. zygis), Myrtaceae (Eucalyptus globulus subsp. maidenii, Eucalyptus radiata, Eucalyptus viminalis) and Pinaceae (Pinus pinaster) were assayed for the release of CCL2 and TNF-α by LPS-stimulated THP-1 cells. B. huillensis, S. africana, S. montana, Th. mastichina and Th. vulgaris EOs showed toxicity to THP-1 cells, at the lowest concentration tested (10 μg/mL), using the tetrazolium dye assay. The most active EOs in reducing TNF-α release by LPS-stimulated THP-1 cells were those of T. capitata (51% inhibition at 20 μg/mL) and L. luisieri (15–23% inhibition at 30 μg/mL and 78–83% inhibition at 90 μg/mL). L. luisieri EO induced a concentration-dependent inhibition of CCL2 release by LPS‑stimulated THP-1 cells (23%, 54% and 82% inhibition at 10, 30 and 90 μg/mL, respectively). These EOs are potentially useful in the management of inflammatory diseases mediated by CCL2 and TNF‑α, such as atherosclerosis and arthritis.